2017
DOI: 10.1653/024.100.0128
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Anaphes chrysomelae (Hymenoptera: Mymaridae) on the Eggs of Chrysolina herbacea (Coleoptera: Chrysomelidae) in Turkey

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…(Anaphes) nipponicus, which was first reported from Japan (Kuwayama, 1932) and is also known in the Oriental region from Fujian in mainland China (Bai, 2007) and Taiwan (Samková et al, 2017). Also, Tarla & Tarla (2017) reported A. (Patasson) lineipennis (Soyka, 1949) [as Anaphes chrysomelae (Bakkendorf, 1960)] from eggs of Chrysolina herbacea (Duftschmid, 1825) (Chrysomelidae) in the Asian part of Turkey, and Lotfalizadeh (2015) listed two unidentified species of Anaphes from Iran.…”
Section: Introductionmentioning
confidence: 99%
“…(Anaphes) nipponicus, which was first reported from Japan (Kuwayama, 1932) and is also known in the Oriental region from Fujian in mainland China (Bai, 2007) and Taiwan (Samková et al, 2017). Also, Tarla & Tarla (2017) reported A. (Patasson) lineipennis (Soyka, 1949) [as Anaphes chrysomelae (Bakkendorf, 1960)] from eggs of Chrysolina herbacea (Duftschmid, 1825) (Chrysomelidae) in the Asian part of Turkey, and Lotfalizadeh (2015) listed two unidentified species of Anaphes from Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Although the species has not been part of Cyprus fauna until now, it is a Mediterranean species that seems to be well adapted to the climatic conditions of Cyprus. In addition, owing to the fact that (i) a large number of its host plants are native to Cyprus or naturalised and are found growing naturally or in cultivated conditions across the Island (Tsintidis et al 2002) and (ii) the species (both larvae and adults) have been found at forest areas, we can safely conclude that it is established. From our observations, the species can cause minor damage on the foliage of its host plants.…”
Section: Discussionmentioning
confidence: 98%
“…As C. americana is a Mediterranean species, its natural enemies are also part of the fauna of Cyprus. Known natural enemies are Anaphes chrysomelae (Bakkendorf) (Hymenoptera: Mymaridae) which parasitised the eggs of C. americana in Italy (Tarla and Tarla 2017) and parasitic flies (Diptera: Tachinidae) which parasitised the larvae, such as Meigenia dorsalis (Meigen, 1824), Meigenia mutabilis (Fallén, 1810), Macquartia dispar (Fallén, 1820), Macquartia tenebricosa (Meigen, 1824) and Macquartia tessellum (Meigen, 1824) . From those enemies, Macquartia tessellum (Meigen, 1824) is present in Cyprus (Bergstrom et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is native to the European region (Al-Nadawi, 2019). In Turkey it is aggressive invasive species, which causes severe damages to various wild and cultivated varieties of mint (Tarla, Tarla, 2017). The damage they cause can be direct or indirect.…”
Section: Discussionmentioning
confidence: 99%